Exclusive Breastfeeding, Nutrition, And Growth: Challenges In Preventing Stunting In Toddlers In South Kalimantan - Pratiwi Puji Lestari; Siti Maria Ulfa; Afiatun Rahmah; Levana Sondakh; Nadiyah Ramadhani; Siti Noor Haliza (HealthCare Nursing Journal, 2026)
Background: This study aimed to analysed the relationship between exclusive breastfeeding and the incidence of stunting in children under five years old. Methods: A case-control design involving 464 toddlers from areas with high stunting prevalence was employed. Results: Statistical analysis revealed no significant relationship between exclusive breastfeeding and stunting (p = 0.3), although descriptively, children who were not exclusively breastfed had a higher incidence of stunting. Additionally, factors such as child’s age, nutritional status based on weight and height, and weight gain showed a statistically significant relationship with stunting (p < 0.05). Conclusion: These findings suggest that stunting prevention requires a comprehensive approach involving not only exclusive breastfeeding but also continuous growth monitoring and attention to environmental and health factors.